ANALISIS KEMAMPUAN MENULIS KARANGAN NARASI MELALUI MEDIA GAMBAR BERSERI MATA PELAJARAN BAHASA INDONESIA KELAS II SEKOLAH DASAR - Faizatul Lailia; Mudzanatun; Moh Aniq Khairul Basyar (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the challenges faced by second-grade students in writing narrative essays, particularly in developing ideas, structuring stories, and applying correct writing rules. The purpose of this study is to describe the effectiveness of using picture series media in helping students develop ideas and structure stories coherently in Indonesian language learning, and to identify the difficulties experienced by students in writing narrative essays. This study employed a qualitative approach with a descriptive approach. The subjects were second-grade students at Peterongan Elementary School in Semarang. Data collection procedures included observation, interviews with teachers and students, tests, and documentation of students' narrative essays. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The results of this study indicate that 1) the implementation of narrative essay writing instruction through picture series media went well, and students demonstrated active involvement throughout the learning process. 2) Picture series media helped students understand story sequences, develop ideas, and structure narrative essays more coherently. Students' writing skills were categorized as adequate with an average score of 69.80. 3) Difficulties experienced by students include confusion in starting to write, difficulty understanding the contents of a series of pictures, limitations in developing ideas into a complete story, and a lack of understanding of writing rules such as the use of letters, spelling, and punctuation. Penelitian ini dilatarbelakangi oleh permasalahan kemampuan menulis karangan narasi pada peserta didik kelas II, terutama dalam mengembangkan ide, menyusun cerita, dan menerapkan kaidah penulisan yang benar. Tujuan penelitian ini adalah untuk mendeskripsikan hasil media gambar berseri dalam membantu peserta didik mengembangkan ide serta menyusun cerita secara runtut dalam pembelajaran Bahasa Indonesia dan mengidentifikasi kesulitan yang dialami peserta didik dalam menulis karangan narasi. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan deskriptif. Subjek dalam penelitian ini adalah siswa kelas II A di SD Negeri Peterongan Semarang. Prosedur pengumpulan data dengan menggunakan observasi, wawancara dengan guru dan peserta didik, tes, serta dokumentasi hasil karangan narasi siswa. Teknik analisis data dilakukan melalui reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian ini menunjukkan bahwa 1) pelaksanaan pembelajaran menulis karangan narasi melalui media gambar berseri berlangsung dengan baik dan peserta didik menunjukkan keterlibatan aktif selama proses pembelajaran. 2) Media gambar berseri membantu peserta didik dalam memahami urutan cerita, mengembangkan ide, dan menyusun karangan narasi secara lebih runtut dengan kemampuan menulis peserta didik berada pada kategori cukup dengan rata-rata nilai 69,80. 3) Kesulitan yang dialami peserta didik meliputi kebingungan dalam mulai menulis, kesulitan memahami isi gambar berseri, keterbatasan dalam mengembangkan ide menjadi cerita utuh, dan kurangnya pemahaman terhadap aturan penulisan seperti penggunaan huruf, ejaan, dan tanda baca.